Korelasi Persepsi Siswa Tentang Kreativitas Guru PAI dengan Hasil Belajar Siswa di SMP Negeri 1 2 X 11 Enam Lingkung - Saputra, Edriagus; Yanti, Novita; Safitri, Winda; Andrianto, Andrianto; Syamsurizal, Syamsurizal (Prodi PAI STAI Sumatera Medan, 2021)
Many educational institutions still do not pay attention to the development of learning media, the impact of learning is not effective. This condition certainly demands the creativity of teachers for the development of learning media. This study aims to determine the correlation of students' perceptions of the creativity of PAI teachers with student learning outcomes in PAI lessons. The method used is quantitative, using a descriptive approach and correlational design. The population of this study amounted to 242 students in class VIII. The results of this study can be stated that (1) Students' perceptions of the creativity of PAI teachers vary widely, meaning that there are students who say that the majority of students think that PAI teachers are creative, this is indicated by the number of student participants getting a score of 75.02 (42.30%) in moderate level. (2) Based on the data of PAI learning outcomes, students vary widely, but most students have high learning outcomes with an average of 77.13. The correlation between students' perceptions of PAI teacher creativity and student learning outcomes is 0.502, which means that students' perceptions of PAI teacher creativity and student learning outcomes have a significant relationship.